2008
DOI: 10.1097/opx.0b013e318181ae4f
|View full text |Cite
|
Sign up to set email alerts
|

Tear Lipocalin and Lysozyme in Sjögren and Non-Sjogren Dry Eye

Abstract: Our data demonstrate a biochemical distinction between the Sjögren's group compared with both KCS and control groups, in that both tear lipocalin and total tear protein were significantly reduced. Although correlations were not found between protein measurements and tear flow, a combination of tests including Schirmer I and quantitation of tear film biomarkers may allow for the identification of SS patients without the need for invasive testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 39 publications
4
35
0
4
Order By: Relevance
“…Lipocalin decrease is in agreement with previous studies performed in patients suffering from Sjogren's Syndrome 28 and Meibomian Gland Dysfunction. 29 To our knowledge, the decrease in the abundances of lipophillin A-B observed in our study has never been described before and may constitute a further progress in the identification of mechanisms responsible for the stability of human tears.…”
supporting
confidence: 82%
“…Lipocalin decrease is in agreement with previous studies performed in patients suffering from Sjogren's Syndrome 28 and Meibomian Gland Dysfunction. 29 To our knowledge, the decrease in the abundances of lipophillin A-B observed in our study has never been described before and may constitute a further progress in the identification of mechanisms responsible for the stability of human tears.…”
supporting
confidence: 82%
“…The total protein was significantly reduced compared to the controls. Previous studies have demonstrated the reduction of major tear proteins such as lysozyme, lactoferrin, lipocalins in DES condition [27]. In this study, differential expression of the proteins in both DES conditions was observed by 2-D approach in tear collected by Schirmer method without pooling of the specimen.…”
Section: Discussionmentioning
confidence: 84%
“…[10] In patients with dry eye syndrome, tear components change in that lactoferrin lysozyme and tear lipocalin are decreased. [30][31][32][33] Therefore, it is reasonable that the bacterial colonization rate in ocular surface increases in patients with dry eye when compared with the normal population. Also, the activity of matrix metalloproteinase-9 (MMP-9) is increased in ocular surface of patients with dry eye.…”
Section: Discussionmentioning
confidence: 99%